Gerakan “ATIKA” Makanan Ibu Hamil di Puskesmas Tungkal II Kabupaten Tanjung Jabung Barat - Arnati Wulansari; Sri Ramadhani; Fajar Rahmawati; Zafira Zafira; Fusvi Sintia Dewi (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Lack of hemoglobin levels in pregnant women is one of the health problems that are prone to occur during pregnancy and can increase the risk of low birth weight babies (LBW), the risk of bleeding before and during delivery, and can even cause the death of mothers and babies if the pregnant woman suffering from severe anemia. Anemia that is often experienced by pregnant women is due to iron deficiency because in pregnant women there is a twofold increase in iron due to an increase in blood volume without plasma volume expansion to meet the needs of the mother and fetal growth. One of the factors that can affect hemoglobin levels is the type of food consumed. Types of foods that are rarely consumed but are very beneficial for pregnant women are liver, eggs, and fish which can be abbreviated as